MULTI-COMPONENT VARIABILITY OF PULSATING VARIABLE STARS OF RV TAURI TYPE - Kudashkina, L. S. (Одеські астрономічні публікації, 2020)
For the group of pulsating variable stars with multi-component variability – which are currently classified as the RV Tau-type stars – the classification based on complexity of the periodograms is discussed. Per- iodograms were computed using the least approximation of the data with a sinusoid. The periodograms previously clas- sified by their shape into three groups according to the pres- ence or absence of certain structures: two peaks in a 2:1 ratio, (biharmonic signal with two waves during a main pe- riod, or the phase curve is significantly asymmetric), the presence of satellites of these peaks at the periodogram in- dicating the result of modulation of characteristics of oscil- lations. Group I includes objects showing the periodogram typical for the RV-type stars, and the ratio of the periods of the two main peaks is indicated. These oscillations appear to be relatively stable during the observations. The Group II includes objects, the periodograms of which contain signs of multi-periodicity or, vice-versa, only one clear peak, instead of two. The presence of multiple peaks may be due to multiple periods, or due to variability of the main period. The Group III includes objects, the periodograms of which are highly noisy, mainly due to a small number of observations or they do not show typical structures of RV- type stars. Such stars may be classified in the catalogue wrongly, so, additional study is needed. For periodogram analysis, the photometric observations from the interna- tional databases of AFOEV, AAVSO and ASAS were used. A least squares method is used for the analysis, to compare the variance in the deviations from the smoothed function with the variance in the initial observations. The mean light curves and the phase plane diagrams dx C ( ф )/d ф” vs” xC (ф) was compiled and analyzed for the values of the periods corresponding to the peaks in the periodograms.